Sex Differences in the Inferior Parietal Lobule - Frederikse, Melissa E.; Lu, Angela; Aylward, Elizabeth; Barta, Patrick; Pearlson, Godfrey (Cerebral cortex (New York, N.Y. 1991), 1999)
The inferior parietal lobule (IPL) – a neocortical region and part of the heteromodal association cortex (HASC) – has been hypothesized to exhibit sexual dimorphism, as do other HASC regions, particularly with regard to asymmetry. Using a reliable method for measuring IPL gray matter volume based upon individual sulcal–gyral landmarks, we measured this region on magnetic resonance imaging scans from a sample of 15 individually matched pairs of normal male and female subjects. Male subjects showed significantly larger left, but not right, IPL volumes when compared to females. Males also showed a leftward (left > right) asymmetry for the IPL, with a less marked opposite asymmetry in females. Such sexual dimorphisms may possibly underlie the subtle cognitive differences observed between the sexes.